What Changes are Mandatory in Breast Surgery Training? An International Survey and Recommendations of the French Academy of Surgery and the Senologic International Society - Tolga Ozmen; Caroline Bouche; Megane Buttignol; Bolivar Arboleda-Osorio; Mauricio Magalhaes Costa; Henry Coudane; Darius Dian; Xishan Hao; Shigeru Imoto; Olivier Jardé; Hubert Johanet; Esther Meka; et al. (European Journal of Breast Health)
Objective: Breast cancer management has significantly evolved, particularly in surgical techniques, but breast surgery training remains unstandardized worldwide. This study, promoted by the Senologic International Society (SIS) and the French National Academy of Surgery (FNAS) aimed to evaluate training variability in the world and to provide ten recommendations to improve breast surgery training. Materials and Methods: A 32-question electronic survey was sent between July-August 2023 to the SIS and FNAS network, covering personal experience, training practices, accreditation programs, and fellowship requirements. Results: A total of 121 breast specialists from 42 countries participated, including mainly general surgeons (56%) and gynecologists (23%). Most respondents (66%) had over 15 years of experience, and 75% were male. While 50% reported that breast surgery fellowships were not mandatory, countries with requirements often stipulated a one or two-year experience and a minimum cases number. Multidisciplinary training was often lacking, with only half of countries requiring rotations in radiology, oncology, or pathology. Disparities in training quality and accreditation were evident, particularly in regions without formal breast surgery programs. Conclusion: High-volume centers and specialized surgeons consistently demonstrated improved outcomes, including lower mortality and recurrence rates for patients treated for breast cancer. Rising breast cancer incidence, combined with advances in surgical and multidisciplinary care, highlights the urgency for standardized training. Evidence shows that structured programs with volume thresholds, multidisciplinary approach, and modern surgical techniques improve patient survival and satisfaction. The survey underscores the need for international guidelines to ensure equitable, high-quality care. SIS and FNAS recommend a standardized breast surgery education framework with ten actionable proposals to address disparities, optimize training, and enhance global care quality.